Principal as A Determinant of Student Disciplinary Behavior - Melliferina, Ratri Avisa; Rani, Putri Rachmah Irfa; Adelweis, Eternity Chitra (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The purpose of this study is to find out the causes of disciplinary violations in Public Middle School X in Central Java.Methodology: This study used qualitative methods using interviews with the school counselors and Focus Group Discussion (FGD) with the school’s student council.Results: The result shows that the involvement of principal is crucial in determining student disciplinary behavior.